2017
DOI: 10.3368/jhr.53.4.1015.7483r1
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond LATE

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…NJCS analyses indicated that Job Corps participation led to substantial short‐run increases in receipt of education/training services and decreases in arrest rates, as well as medium‐run improvements in labor market outcomes and decreases in receipt of public benefits (Chen et al, 2018; Schochet et al, 2001). In addition, youth who participated in Job Corps for longer periods also realized larger gains in terms of postparticipation earnings (Flores et al, 2012).…”
Section: Background On Job Corpsmentioning
confidence: 99%
See 1 more Smart Citation
“…NJCS analyses indicated that Job Corps participation led to substantial short‐run increases in receipt of education/training services and decreases in arrest rates, as well as medium‐run improvements in labor market outcomes and decreases in receipt of public benefits (Chen et al, 2018; Schochet et al, 2001). In addition, youth who participated in Job Corps for longer periods also realized larger gains in terms of postparticipation earnings (Flores et al, 2012).…”
Section: Background On Job Corpsmentioning
confidence: 99%
“…Job Corps is one of the largest youth programs outside the traditional K–12 schooling system. The National Job Corps Study (NJCS), a large‐scale experimental evaluation conducted in the mid‐1990s, found that Job Corps helped improve medium‐term (but not long‐term) work and earnings outcomes for youth and helped reduce both criminal activity and receipt of certain forms of public assistance (Chen et al, 2018; Schochet et al, 2001, 2008). Further, longer participation in academic and vocational instruction in Job Corps (which averaged around 7 months for youth in the NJCS) was linked to larger increases in postparticipation earnings (Flores et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that discrete relaxations of misspecified models have been entertained in various existing papers; see, for instance, Manski and Pepper (2000, 2009), Blundell et al (2007), Kreider, Pepper, Gundersen, and Jolliffe (2012), Chen, Flores, and Flores‐Lagunes (2018), Kédagni (2023), Mourifié, Henry, and Méango (2020), among many others. In these papers, when the initial model is too stringent, they suggested alternative weaker assumptions that are believed to be more compatible with the empirical application under scrutiny and for which the identified/outer set is not empty.…”
Section: Introductionmentioning
confidence: 99%